2013
DOI: 10.1057/ejis.2012.45
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting IS business value research: what we already know, what we still need to know, and how we can get there

Abstract: The business value of investments in Information Systems (IS) has been, and is predicted to remain, one of the major research topics for IS researchers. While the vast majority of research papers on IS business value find empirical evidence in favour of both the operational and strategic relevance of IS, the fundamental question of the causal relationship between IS investments and business value remains partly unexplained. Three research tasks are essential requisites on the path towards addressing this epist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
354
0
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 317 publications
(413 citation statements)
references
References 222 publications
8
354
0
7
Order By: Relevance
“…Previous research has examined the substantial body of IS literature on value and criticized how the discussion frays into many lines of thought in various directions that make the value construct ambiguous and fuzzy (Schryen, 2013). Our action research found that this characterization is also prevalent in practice (particularly in public organizations).…”
Section: Develop Social Commitmentmentioning
confidence: 74%
See 3 more Smart Citations
“…Previous research has examined the substantial body of IS literature on value and criticized how the discussion frays into many lines of thought in various directions that make the value construct ambiguous and fuzzy (Schryen, 2013). Our action research found that this characterization is also prevalent in practice (particularly in public organizations).…”
Section: Develop Social Commitmentmentioning
confidence: 74%
“…In the substantial body of IS literature on value, the discussion frays into many lines of thought in various directions that 4 make the value construct ambiguous and fuzzy (Schryen, 2013). In addition to construct ambiguity, Schryen (2013) points to a neglected disaggregation of IS investments and that the value creation process is a grey box. In the following, we present the literature on IS value according to three dimensions that reflect key differences in the fundamental assumptions and understandings of IS value.…”
Section: Is Value Creationmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, researchers have identified that the effects of investments on indicators of value creation such as stock returns and stock risk are not direct; rather, those effects are mediated by their effects on variables such as customer satisfaction (Fornell et al, 2006(Fornell et al, , 2009. Researchers have also documented the value of being a data-driven organisation and shown that organisations with better information management capabilities achieve improved performance in many different ways (Mithas et al, 2011;Mithas et al, 2012;Saldanha et al, 2013;Schryen, 2013). Mithas et al (2013) and Gillon et al (2014) identify six pathways to value through the use of analytics-based capabilities, namely, Adding volume and growth, Differentiating, Reducing costs, Optimising risks, Improving industry structure (also innovating with products and services), and Transforming business models and business processes for continued relevance in a changing landscape (captured in the acronym ADROIT).…”
Section: Directions For Practicementioning
confidence: 99%